EDUCAÇÃO FINANCEIRA: CONHECIMENTOS E COMPORTAMENTOS DOS ACADÊMICOS DE UMA INSTITUIÇÃO DE ENSINO SUPERIOR PRIVADA (REMUNOM, 2025)
The present work addresses the study of the knowledge and behaviors of academics of a private higher education institution, regarding financial education. The general objective of the study is to discuss the importance of financial education for students of a higher education institution, with the following specific objectives: to identify the number of students who organize themselves financially, to evaluate the level of knowledge that students have about education financial and verify the use of software or applications for financial control. The theoretical framework was based on the concepts addressed by Neto (2014), Lucci et al (2006), Jacob, Hudson and Bush (2000), Lelis (2006), Kempson (2009), Lusardi (2015), Fernandes and Candido (2014), Isoppo, Zilli and Biff (2019), through the topics: Economic Thoughts, Contextualization of Financial Education, Importance of Financial Education and Financial Education in Brazil. The research is classified as applied, qualitative and quantitative, descriptive and field, and the data used were obtained from a research carried out through Google Form, which contributed to the conclusion that most students of the financial institution recognize the importance of Financial Education, but do not apply its aspects.   are not financially organized, among other aspects, which has several consequences, such as the high debt level.